The GOVERNANCE ANALYSIS, EXTERNAL WARRANTY, COMPANY CHARACTERISTICS AND BANKRUPTCY AGAINST SUSTAINABILITY REPORT - Malau, Melinda (Universitas Kristen Indonesia, 2017)
The research purposed to analyze the governance, external assurance, firm-level characteristics and financial distress on the sustainability reporting. The method used in this study are multiple regression analysis using Eviews 9. The samples used in this research are 242 which is the data of 121 manufacturing companies listed in Indonesia Stock Exchange from 2014-2015. The results show that governance committee, sustainability report assurance provider, number of members on the audit committee and the number of members on the board of directors as firm-level characteristics have a significant positive effect on the sustainability reporting. Financial distress has a significant negative effect on the sustainability reporting. Operating cash flow has not a significant effect on the sustainability reporting, whereas log total asset has significant positive effect on the sustainability reporting. Keywords: governance; external assurance; firm-level characteristics; financial distress; sustainability reporting